LITERATURE REVIEW : Pengaruh Aquatic Plyometric Training Terhadap Kecepatan Berlari Pada Pemain Basket - Annida Hasna Fadhillah (2020)
Objective: Basketball always been a popular sport and loved by the public. In basketball, running speed is very important for move the ball from one place to another. So, maximum running speed is required. This study aims to examine the literature, journals, articles or research results with the topic of the influence of aquatic plyometric training on running speed in basketball players. Method: Search for sources of literature, journals, articles, research results in several databases such as Google Schoolar, PubMed, Science Direct and Plos One by using certain keywords in the period 2012-2020. From the literature search results, 3 articles met the source inclusion criteria. The methodological quality assessment of 3 articles was assessed using the Scimago Journal & Country Rank (SJR). Analysis of 3 journals was carried out based on the suitability of the topic, the research methods used, subject, interventions, instruments/parameters, and the results of each article. Results: After reviewing the literature as many as 3 articles showed that Aquatic plyometric training cannot improve the running speed a person . Conclusion: Aquatic plyometric training cannot significantly increase the running speed for basketball players.